Pemanfaat Limbah Rumah Tangga Sebagai Pupuk Organik Berbahan Baku Air Cucian Beras Kepada Masyarakat di Kelurahan Lobu Sona Kecamatan Rantau Selatan - Yelfi Yana Linda Br Sijabat; Rahmania, Rahmania; Sibuea, Nunti (Universitas Mataram, 2024)
Currently, environmentally friendly agriculture is accompanied by high demand for organic products. There are various types of household waste, but around 85% of household waste is organic waste and the rest is inorganic waste. Processing this waste into products with high economic value, such as liquid organic fertilizer, is one of the solutions that can be done so that the waste that is most produced by households is rice washing water which can be used as the main raw material in making liquid organic fertilizer. This activity uses counseling and training methods for housewives and the local community. Based on the evaluation results from the practical session, it can be concluded that this activity as a whole has succeeded in improving the ability of participants in making liquid organic fertilizer and how to use it on plants. The enthusiasm of the participants for the training was seen during this training activity. This was proven when the speaker presented data on the results of the trial of the use of liquid organic fertilizer on plants.